2018
DOI: 10.1080/1028415x.2018.1511027
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced activity of superoxide dismutase is a common response to dietary and genetically induced increased cholesterol levels

Abstract: Hypercholesterolaemia could potentiate brain dysfunction and neurodegenerative processes via oxidative stress, and activity of mitochondrial SOD2 may play a key role in this process. Our findings suggest that preventing/reducing mitochondrial oxidative stress may represent a common approach against neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…In NPC1 patient-derived fibroblasts, downregulation of the gene expression and a diminished protein level of the SOD2 were also found [ 26 , 27 ]. However, Dominko and colleagues [ 22 ] found changes neither of the SOD1 nor the SOD2 protein level in NPC1-deficient CHO cells, although they detected changes in SOD activity [ 22 ]. Unexpectedly, we did not observe any alterations in the regulation or expression of SOD1 and SOD2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In NPC1 patient-derived fibroblasts, downregulation of the gene expression and a diminished protein level of the SOD2 were also found [ 26 , 27 ]. However, Dominko and colleagues [ 22 ] found changes neither of the SOD1 nor the SOD2 protein level in NPC1-deficient CHO cells, although they detected changes in SOD activity [ 22 ]. Unexpectedly, we did not observe any alterations in the regulation or expression of SOD1 and SOD2.…”
Section: Discussionmentioning
confidence: 99%
“…Similar hallmarks of OS can be detected in different in vitro models. In NPC-deficient neuroblastoma cells, higher ROS levels were detected by flow cytometry measurements [ 13 , 22 ]. Dominko and colleagues [ 22 ] pointed out differences in the defense system of the NPC1-deficient CHO cells represented by lower GSH content, decreased catalase activity and elevated SOD activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we noticed a significant and positive correlation between SOD and cholesterol, HDL-C and LDL-C in PD patients. It has been shown that increased cholesterol, either in vivo in cholesterol-fed wt mice or in vitro in genetically induced cholesterol accumulation due to NPC1 loss-of-function, could potentiate SOD activity, suggesting that SOD might be a prime target and the first defense mechanism of oxidative stress response upon increased cholesterol (Dominko et al, 2018). Multiple lines of evidence already indicate that a high level of LDL-C could cause the free radical formation and excessive oxidative stress, which initially leads to a progressive increase in endogenous enzymatic scavengers like SOD (Gupta et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, SOD mimetic has been successfully used to prevent the extent of inflammation (De Lazzari et al, 2018;Ren et al, 2018). As mentioned above, SOD is the prime target and the first defense mechanism of oxidative stress response upon increased cholesterol /LDL-C (Gupta et al, 2009;Dominko et al, 2018), which may prevent the inflammatory response caused by cholesterol /LDL-C to some extent. Therefore, there seems to be a strong and complicated interaction between hsCRP/cholesterol/LDL-C pro-inflammatory function and SOD anti-inflammatory function, which may influence the cognitive dysfunctions in PD patients.…”
Section: Discussionmentioning
confidence: 99%